Recognition and duration of larval instars of banana weevil, Cosmopolites sordidus Germar, in Uganda - Gold, Cliford S.; Neyeme, P.S.; Coe, R. (1999)
Analysis of head capsule widths of banana weevil larvae was carried out to determine the number and recognition of instars. The analysis involved model fitting to frequency distributions of head capsule measurements of laboratory-reared and field-collected larvae. The laboratory population revealed developmental polymorphism, with larvae passing through 5-7 instars. The model fitted Gaussian curves with five peaks for laboratory samples and six peaks for field samples. Mean head capsule widths for the first four instars showed close agreement among both laboratory and field-collected populations. Variability appeared greater among field populations, resulting in a higher probability of misidentification. The method of analysis was not sufficiently sensitive to separate later instars. Plotting mean head-capsule widths against instar number showed a geometric curve to be the best fit, but with only approximate conformity to Dyar's rule. The duration of banana weevil immature stages was determined under ambient conditions in three experiments. Most eggs hatched within 5.5--8.0 days. Using a developmental threshold of 12C, thermal requirements (92.8-95.9 degree-days) appeared similar to those established for a West African population. Larvae passed through 5-8 instars, with 74 % pupating after six instars. Larvae completed development in 20-41 (most less than 30) days and spent 3-5 days in each instar. The pre-pupal period averaged 4.6 days, while the pupal stage averaged 7.0 days. Overall, the egg to adult period lasted 6-8 weeks. Rearing methods influenced the number of instars and the length of the larval period. Applications of these data for life-table studies are discussed.